Edukasi Tata Cara Wudhu dan Shalat sebagai Sarana Pembentukan Karakter Religius Siswa SD Palasari 3 Bandung - Nurdinar, Dewi; Alawiyah, Tuti; Mukhlishah; Amelia, Iqlima; Supriatna, Riyan; Hutri Niaga, Andfrean; Majid, Abdul; Nurjanah, Kania; Lathifa Halis, Putri; Alamsyah, Kevin; Gumilar, Yogi; Hafni Sulisti, Halida (LPPAIK Universitas Muhammadiyah Bandung, 2024)
This research aims to improve students' understanding and practice of wudhu and prayer at SD Palasari 3 Bandung through an interactive educational approach. Considering the importance of wudhu and prayer as a means of fostering religious character, this activity employs various creative methods such as videos, live demonstrations, clapping, songs, and educational games. The study was conducted using action research methods, involving third and sixth-grade students as subjects. The results show that the interactive methods effectively enhanced students' understanding and skills in performing wudhu and prayer, as well as instilling discipline, focus, and responsibility. Moreover, the students demonstrated a high level of engagement in learning, particularly through the enjoyable approach. This research confirms that varied and engaging religious education can significantly contribute to the formation of students' religious character.